Identical eaudiobook - Hopkins, Ellen (HighBridge Audio, 2008)
In the latest hard-hitting YA novel by the New York Times bestselling author, sixteen-year-old identical twin girls must come to terms with their abusive father. Kaeleigh and Raeanne are sixteen-year-old identical twins, the daughters of a district court judge father and politician mother running for Congress. Everything on the surface of their lives seems Norman Rockwell perfect, but underneath run deep and damaging secrets. Kaeleigh is the good girl-her father's perfect flower, something she has tried so hard to be since she was nine and he started sexually abusing her. She cuts herself and vomits after every binge, desperate to feel something normal. Raeanne uses painkillers, drugs, alcohol, and sex to numb the pain of not being Daddy's favorite. Both girls must figure out how to become whole, but how can they when their world has been torn to shreds? Writing in her characteristic narrative poetry style, Ellen Hopkins shows once again how well she knows today's teens and the issues that matter to them.